Clinical case of the infant with primary immunodeficiency - G.R. Muratov; M.M. Popov; O.V. Volobuieva; T.V. Frolova; O.M. Savvo; Yu.V. Кarpushenko; K.Yu. Pashchenko; A.G. Soloviova (Journal of V. N. Karazin Kharkiv National University: Series Medicine, 2025)
Background. Primary immunodeficiency is a group of more than 550 rare genetic diseases characterized by reduced or absent resistance to infectious agents involving all parts of the immune system. According to the European Association of Immunologists, 70–90% of patients with PID remain undiagnosed.